A review on battery thermal management and its digital improvement‐based cyber hierarchy and interactional network. (19th April 2022) - Zhang, Yulong; Liang, Fengwei; Li, Shen; Zhang, Cheng; Zhang, Shifang; Liu, Xinhua; Zhao, Shupeng; Yang, Shichun; Xia, Yuhua; Lin, Jiayuan; Guo, Bin; Cheng, Hanchao; et al.
Summary: The temperature has a significant influence on the performance of lithium‐ion batteries (LiBs). Meanwhile, the heat‐generated accumulation in the battery can trigger the battery's thermal runaway. Hence, the battery thermal management system (BTMS) is essential to ensure the safe and reliable operation of the battery. This paper comprehensively reviewed key technologies of BTMS and proposed a novel digital solution to improve the battery system performance. Firstly, the heat generation mechanisms and the thermal models were reviewed. Then, this paper focuses on a review of liquid cooling thermal management methods. Simultaneously, the solid‐liquid phase change gas‐liquid phase change is also summarized in the phase change material cooling system, and a summary is presented for the existing novel phase change cooling systems. Additionally, the preheating methods to heat the LiBs at low temperatures and the emergency battery thermal barriers upon thermal runaway were discussed. Eventually, a new approach for the BTMS leveraging from the Cyber Hierarchy and Interactional Network framework is indicated and constructed the digital twin reflecting physical battery to improve the LiBs temperature control strategies. Besides, this paper provides a new direction for the design of BTMS through vehicle‐side sensing, edge computing, and cloud‐based digital twin three levels. Novelty Statement: A state‐of‐the‐art digital solution for battery thermal management system. A comprehensive review of battery thermal management methods. A novel guidance scheme for the design of a battery thermal management system. Abstract : Presenting a Cyber Hierarchy and Interactional Network CHAIN)‐based battery thermal management solution and a comprehensive battery thermal management overview